#Healthpromotion: A qualitative exploration of how dietitians can use social media to positively influence women aged 18–35 years. Issue 4 (9th September 2022) - Shine, Danielle; Minehan, Michelle; Knight‐Agarwal, Cathy
Abstract: Aims: To understand how young adult women use social media, including which nutrition and health‐related content they prefer to view and why. Findings are intended to support dietitians to use social media more effectively for health promotion to reach, educate and positively influence young adult women. Methods: Qualitative research was conducted through semi‐structured interviews involving 10 women aged 18–35 years via Zoom videoconferencing. The interviews were recorded, transcribed verbatim and analysed using an interpretative phenomenological approach. Results: Young adult women use social media daily to view a wide variety of content, including nutrition and health‐related content. Three themes were identified: authenticity, engaging content, and affecting trust through selling products. Conclusion: To effectively use social media for health promotion, dietitians need to share their authentic voice while maintaining professional standards. Recommendations for effective social media engagement include using engaging content, infographics, and videos with closed captions. More research is needed to assess whether health promotion deployed via social media is effective at increasing nutrition knowledge, improving health literacy, and producing behaviour change.